PENGARUH MAKRO EKONOMI TERHADAP INDEKS SAHAM DI JAKARTA ISLAMIC INDEX (JII) - Masagus Zahidal Hakim (I-Economics: A Research Journal on Islamic Economics)
This research aim is to analyze the impact of macroeconomics variable to Islamic stock’s index in Indonesia. The macroeconomic variables are Money supply (M2) BI-rate, inflation, exchange rate. The methods that used in this research is error correction model (ECM) to analyze the short-run and long-run impact of macroeconomics variables to Islamic stock’s index. The result shown There is no short-term relationship between the variable Money Supply, Inflation, Exchange Rates, interest rates but the variable is corrected in a long-term relationship. Money Supply, inflation, BI-Rate and exchange rate influence the to Islamic stock’s index in long -run.